Economic growth theory : capital, knowledge, and economic structures - Zhang, Wei-Bin, 1961- (Routledge, Taylor & Francis Group, 2018)
"This book develops a new theoretical framework to examine the issues of economic growth and development. Providing analysis of economic dynamics in a competitive economy under government intervention in infrastructure and income distribution, the book develops a unique analytical framework under the influence of traditional neoclassical growth theory. However, in a departure from neoclassical growth theory it examines both the Solow-Swan and the Ramsey growth models, introducing a utility function which treats consumer choices in ways critically different to previous approaches. Using practical examples and models the book demonstrates how this new direction can effectively analyze the key issues of economic growth, in a compact and comprehensive manner."--Provided by publisher